Crystal structure, Hirshfeld surfaces analysis, vibrational spectroscopy, thermal behavior, and DFT study of S-triazine perchlorate - Chaima Zouari; Thameur Dammak; Jerome Lhoste; Mohamed Boujelbene; Mohamed Abdelhedi (Results in Chemistry)
The hybrid material [C3H4N3]ClO4 was synthesized at ambient temperature using a slow evaporation method. Single-crystal X-ray diffraction reveal edits monoclinic structure with a P21/n space group. Hirshfeld surface analysis elucidated the intermolecular interactions, highlighting hydrogen bonds between the S-triazine cations and tetrahedral perchlorate (ClO4−) anions. Vibrational modes were investigated using Raman and infrared spectroscopy, providing insights into the compound’s molecular structure. Thermogravimetric analysis assess edits thermal stability, while UV–Vis diffuse reflectance spectroscopy identified a significant absorption band at 304 nm (4.07 eV). Computational studies employing density functional theory (DFT) complemented the experimental findings, corroborating the material’s structural and electronic properties.